Comparative analysis of water-ice cold storage devices - А. V. Baranenko; V. V. Tamarov; M. V. Korolenko (Вестник Дагестанского государственного технического университета: Технические науки, 2025)
Objective. The use of cold accumulation in cooling systems increases their efficiency, reduces the power of the installed equipment, equalizes the load on the electrical grid and ensures an economic effect. Method. The study is based on the methods of thermodynamic analysis of technical characteristics of various modifications of water-ice cold accumulators. Result. The analysis of technical characteristics of three types of ice accumulators was carried out: with water freezing on the heat-exchange surface (type 1), with water freezing in a tank (type 2) and in containers (type 3). Recommendations for their use were developed and promising areas of scientific research were determined. Specific parameters were compared: volume, cooling capacity and metal consumption. Conclusion. Devices of the second and third types have a number of advantages over devices of the first type: they are more compact, have a metal consumption 1.5–3 times lower. The efficiency of ice accumulators of all types in terms of specific cooling capacity is approximately the same and is within the range of 0.08–0.3 kW/kWh. Accumulators of the third type are of interest. To create them, it is necessary to carry out a set of analytical and experimental studies.